2019
DOI: 10.1111/jep.13254
|View full text |Cite
|
Sign up to set email alerts
|

Association of alprazolam with major cardiovascular events in patients with hypertension

Abstract: Rationale: Anxiety is a mediator for emotional reactivity and acute blood pressure elevations, which are associated with an increased risk of cardiovascular death.Alprazolam is a common medication for anxiolysis. We hypothesized that alprazolam usage can reduce the risk of major adverse cardiovascular events (MACEs) in patients with hypertension.Methods: A retrospective cohort study was performed using datasets from Taiwanese Health and Welfare Data. Patients with hypertension were divided into exposed (Alpraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Most neuroprotective drugs are antioxidants, and benzodiazepines have been shown to have an antioxidant effect. The neuroprotective effect of low-dose benzodiazepines (Liu et al, 2016 ) and the improvement of some classical risk factors such as hypertension (Yeh et al, 2020 ) might explain our results. This neuroprotective effect could be attributed to its ability to mitigate chronic inflammation levels (Dominguini et al, 2021 ).…”
Section: Discussionmentioning
confidence: 59%
“…Most neuroprotective drugs are antioxidants, and benzodiazepines have been shown to have an antioxidant effect. The neuroprotective effect of low-dose benzodiazepines (Liu et al, 2016 ) and the improvement of some classical risk factors such as hypertension (Yeh et al, 2020 ) might explain our results. This neuroprotective effect could be attributed to its ability to mitigate chronic inflammation levels (Dominguini et al, 2021 ).…”
Section: Discussionmentioning
confidence: 59%
“…In addition, the alprazolam has been shown to be as effective as captopril in reducing BP in emergency services [48]. Minimal sedation with alprazolam has already been associated with a reduced risk of serious cardiovascular events, such as hemorrhagic stroke and acute myocardial infarction, particularly in the elderly [49].…”
Section: Hypertensive Crisismentioning
confidence: 99%
“…A relatively recent study of cardiovascular outcomes in hypertensive patients exposed to alprazolam showed that this group was associated with a significantly reduced risk of major adverse cardiovascular events, including ischemic stroke, hemorrhagic stroke, myocardial infarction, sudden cardiac death, and all-cause mortality, probably by virtue of its antianxiety action 6 . These findings prompt cardiologists to use alprazolam as an add-on agent in their patients, especially those with anxiety symptoms.…”
mentioning
confidence: 99%